KECERDASAN EMOSI DENGAN PRESTASI BELAJAR SISWA TUNARUNGU DI SMPLB KARYA MULIA - Sonia Ardianie, Elisabet Widyaning Hapsari (EXPERIENTIA : Jurnal Psikologi Indonesia, 2012)
Learning achievement is the result of study that shows the level of individual mastery of the material taught. One factor that may affect the achievement of learning is emotion Goleman (2002: 17). Noble’s work on the school SMPLB Surabaya where students have a limited hearing that the learning achievement of deaf students were allegedly also associated with emotional intelligence possessed by students. This study aims to look at the relationship between emotional intelligence with learning achievement in hearing impaired students in schools SMPLB Karya Mulia Surabaya. The study subjects (N = 41) were students of Surabaya Majesty SMPLB using total study population sampling technique that capture the. Data were collected by using a scale of emotional intelligence to uncover the emotional intelligence of students while learning achievement revealed by looking at the total value of the first semester report cards during the school year 2011-2012. Data were analyzed with non parametric Kendall’s tau_b, with the help of SPSS For Windows Version 17.0. The analysis of data showed the correlation coefficient rxy = 0296 with p = 0.008 (p